2006
DOI: 10.1111/j.1442-2050.2006.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Black esophagus: report of six cases and review of the literature, 1963–2003

Abstract: Black esophagus is the uncommon endoscopic finding of extensive black discoloration of the esophageal mucosa, usually from acute esophageal necrosis. Six cases of black esophagus were seen at Mayo Clinic (Rochester, Minnesota, USA) from 1997 through 2003, and 46 cases were reported in the English-language literature from 1963 through 2003. We studied the demographics, clinical features, and outcomes of these 52 cases of black esophagus. Age and sex were known for 50 patients: the mean (SD) age was 65 years (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
82
0
23

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 27 publications
2
82
0
23
Order By: Relevance
“…AEN was first diagnosed endoscopically by Goldenberg and colleagues in 1990 [1]. To date there have been fewer than 90 cases reported, and the mortality rate in theses series was 32% to 36% [2][3][4]. The longest follow-up reported was 6 months.…”
mentioning
confidence: 91%
“…AEN was first diagnosed endoscopically by Goldenberg and colleagues in 1990 [1]. To date there have been fewer than 90 cases reported, and the mortality rate in theses series was 32% to 36% [2][3][4]. The longest follow-up reported was 6 months.…”
mentioning
confidence: 91%
“…Herpetic lesions of the esophagus are commonly seen as discrete ulcerations on an inflamed and friable mucosa at endoscopy mostly in the distal esophagus unlike in our patient where there was only desquamation with distal few centimeters of esophagus being spared [8,9,11] . In candidal esophagitis, the esophageal mucosa is typically friable and erythematous with ulcers covered by thick adherent white exudates [6,10] .…”
Section: Discussionmentioning
confidence: 65%
“…To confirm the presence of invasive candidal esophagitis, Candida spp. are seen along with squamous cells and invading hyphae on smears [2,4] .Viral culture, immunohistochemistry, PCR and serology have been used for the diagnosis [11,19] . Herpetic esophagitis is usually regarded as a self-limited illness in otherwise healthy individuals [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tissue compression is not a probable cause of skin necrosis in this patient. As some other studies reported necrotizing infections in connection with Candida in different regions of the body, 18,19 we suspect a necrotizing candidiasis also in this case.…”
Section: Discussionmentioning
confidence: 67%